Prevalence of physical inactivity and associated factors among adolescents from public schools in Uruguaiana, Rio Grande do Sul State, Brazil - Gabriel Gustavo Bergmann; Mauren Lúcia de Araújo Bergmann; Alexandre Carriconde Marques; Pedro Curi Hallal (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
This study aimed to identify the prevalence of physical inactivity and associated factors in adolescents, using a cross-sectional design with a sample of 1,455 adolescents (741 females). Data were collected using a questionnaire consisting of socio-demographic, perceptual, and behavioral variables. Physical activity was estimated with the Physical Activity Questionnaire for Older Children and Adolescents. Prevalence of physical inactivity was 68% (95%CI: 65.6%-70.4%). The following variables remained associated with physical inactivity in the adjusted analysis (p < 0.05): living in an apartment, female gender, older adolescents, lower self-rated physical activity compared to peers, low perception of maternal physical activity, passive commuting to school, non-participation in physical education at school, non-enjoyment of physical education classes, and limited involvement in other types of physical exercise besides physical education at school. There were a high proportion of inactive adolescents. Strategies to prevent physical inactivity in adolescents should be elaborated with a central role for the school and family.